Om bygningsarkæologien i arkitektfagets uddannelse og praksis - Bock, Lars Nicolai (Hikuin, 2011)
Building archaeology in education and practice of the architectural profession By Lars Nicolai Bock This article discusses how building archaeology relates to the architectural profession and the education of architects – mostly in a Danish context. The text is based on the authors experience as an assistant professor at the Aarhus School of Architecture as well as from his professional life. Building archaeology is a discipline practiced by a number of professions, most of these academic. One can speak of a situation where professional roles and their relation to field objects are rather unclear and need to be discussed. The different professions – that is for instance architects, archeologists, historians, art historians, conservators etc. – deal with objects that are different and alike. This situation calls for clarification and cooperation. The goal for a discussion could be an optimized education, practice and use and of the different professions and a more intense interdisciplinary and multidisciplinary use of the many special competencies. In Denmark, traditions coming from the academy of art have had a strong influence on the education of architects. This tradition, to a certain degree, rules out the more research-minded approach to for instance conservation and preservation. In the field of conservation and preservation there is a very strong need for knowledge as background for architectural projects. Knowledge about a historic building and its different periods is the background and prerequisite for defining both values and cultural significance. An architectural project that is not based on conscious and transparent valuation of the object – both as a whole and in details – will often loose the historic and architectural significance of the building. There is an increasing need for optimized skills, more knowledge as well in the field of research as in the field of design dealing with historic structures. There is a need for better educations, cooperation, interdisciplinary and multidisciplinary practice in the series of professions that deals with building archeology, conservation and preservation of historic buildings in the future.